2013
DOI: 10.1021/pr400861m
|View full text |Cite
|
Sign up to set email alerts
|

Comparative N-Glycan Profiling of Colorectal Cancer Cell Lines Reveals Unique Bisecting GlcNAc and α-2,3-Linked Sialic Acid Determinants Are Associated with Membrane Proteins of the More Metastatic/Aggressive Cell Lines

Abstract: Advances in colorectal cancer (CRC) diagnosis will be enhanced by development of more sensitive and reliable methods for early detection of the disease when treatment is more effective. Because many known disease biomarkers are membrane-bound glycoproteins with important biological functions, we chose to compare N-glycan profiles of membrane proteins from three phenotypically different CRC cell lines, LIM1215, LIM1899, and LIM2405, representing moderately differentiated metastatic, moderately differentiated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 46 publications
7
105
0
Order By: Relevance
“…Further, our mass spectrometry analysis showed that the sialic acids on bisected N-glycans were almost in an ␣2,6-linkage. Consistently, a recent study on the N-glycan profiling of a GnT-III highly expressed colorectal cancer cell line using the method of porous graphitized carbon LC-ESI-MS/MS indicated that the bisecting GlcNAc structures accounted for 38% of total relative abundance of complex and hybrid glycans, but no ␣2,3-linked sialic acids were detected on the bisected N-glycans (17). All these results suggest that the biantennary or hybrid bisecting structures may not favor the subsequent transfer of ␣2,3-linked sialic acids as compared with the nonbisecting chains, but it does not mean that ␣2,3-sialyltransferases could not use the bisecting structures as substrates at all because traces of the bisecting N-glycans that carry ␣2,3-linked sialic acids have been detected recently in ovarian cancer cell lines, although they are much less than ␣2,6-sialylated bisecting N-glycans (16).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Further, our mass spectrometry analysis showed that the sialic acids on bisected N-glycans were almost in an ␣2,6-linkage. Consistently, a recent study on the N-glycan profiling of a GnT-III highly expressed colorectal cancer cell line using the method of porous graphitized carbon LC-ESI-MS/MS indicated that the bisecting GlcNAc structures accounted for 38% of total relative abundance of complex and hybrid glycans, but no ␣2,3-linked sialic acids were detected on the bisected N-glycans (17). All these results suggest that the biantennary or hybrid bisecting structures may not favor the subsequent transfer of ␣2,3-linked sialic acids as compared with the nonbisecting chains, but it does not mean that ␣2,3-sialyltransferases could not use the bisecting structures as substrates at all because traces of the bisecting N-glycans that carry ␣2,3-linked sialic acids have been detected recently in ovarian cancer cell lines, although they are much less than ␣2,6-sialylated bisecting N-glycans (16).…”
Section: Discussionsupporting
confidence: 63%
“…Recently, the expression of both GnT-III and ST6GAL1 was found up-regulated in the human ovarian cancer and knockdown of ST6GAL1 significantly inhibited cell migration (16,40). One group last year showed a highly metastatic colorectal cancer cell line, which contained an abundance of bisecting GlcNAc glycans (17). This made them somewhat surprised because GnT-III is usually considered to be a tumor metastasis suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in high mannose structures have been previously reported in breast cancer progression in mouse models, colorectal cancer cell lines and hepatocellular carcinoma, among others (42)(43)(44). The increased expression of highmannose glycans could suggest a premature termination of the glycosylation pathway during glycan synthesis.…”
Section: Table 1 N-glycan Structures Assigned By Pgc-lc-esi-ion Trap mentioning
confidence: 71%
“…Intrigued by the temporal and compartment-specific biosynthetic route for paucimannosylation in neutrophils proposed here, we are investigating whether paucimannosylation is unique to neutrophils or common across cell types. We have recently reported that cultured human colon and breast cancer epithelial cells produce paucimannosidic epitopes (6,60), albeit in lower quantities (typically less than 15-20% of the total N-glycome), supporting a possible oncofetal antigen potential of paucimannosylation (12) and the possible molecular and functional similarity of neutrophils and epithelial cells (58). However, the lack of azurophilic granules in epithelial cells implies that production, storage, and secretion of paucimannosidic proteins may be facilitated by other mechanisms in these systems.…”
Section: Discussionmentioning
confidence: 99%